Evaluating the impact of pharmacist health education on the perceptions of the pharmacist's role among women living in a homeless shelter - Tsu L; Buckley K; Nguyen S; Kohn J (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Objectives: To determine the impact of pharmacist-provided educational seminars on the participant's perception of the pharmacist's role in providing women's health education. Secondary objectives include the participant's level of perceived benefit from the information provided during each presentation, as well as determining characteristics of participants who are interested in attending seminars. Methods: This is a prospective study conducted within a homeless women's shelter in Phoenix, Arizona. Pharmacists and pharmacy students provided 10 monthly educational seminars on topics related to women's health. Participants completed a pre- and post-seminar survey regarding their perceptions of the presentations and pharmacists. Results: Fifty-six participants attended at least one of 10 seminars from January to November 2014. The average age was 46 years old, taking approximately 3 medications, and 66% completed a high school degree or lower. Prior to the presentations, 30% of participants agreed or strongly agreed that they would seek advice from a pharmacist on the topic presented, which increased significantly to 82% of participants after the presentation (p<0.001). Similarly, 55% of participants rated themselves as agreeing or strongly agreeing with being knowledgeable on the topic presented prior to the presentation, and this increased significantly to 77% after the presentation (p=0.001). After attending the educational session, 70% of participants agreed or strongly agreed that they would make changes to their health, and that they would attend an additional session. The participants noted their increased learning about the topic, the clarity of visual aids and presentation, and knowledge of the presenters as the best parts of the presentation. Conclusion: Pharmacist's participation in providing educational seminars in the homeless women's population increases the participant's knowledge and perception of the pharmacist's role within the population. Future studies can further investigate an evolving role of pharmacists in optimizing healthcare in the homeless population.